Social Security : The Story of British Social Progress and the Beveridge Plan - Great Britain. Inter-departmental Committee on Social Insurance and Allied Services; Davison, Ronald C. (Ronald Conway), 1884- (London : G.G. Harrap and Co., 1943)
1943 1943 1940s 3 preliminary leaves, 9-62 pages : illustrations, diagrams 1936 [Picture] Old age, illness [Picture] Large family [Picture] Low Wages [Picture] Unemployment [Picture] Others [Picture] 15X/2/566/303